Technology for the oil spills clean-up which provides preliminary accumulation of sorbents into the area of emergence and localization oil spills - Soroka, M. L.; Yaryshkina, L. A. (Science and Transport Progress, 2012)
Introduction: The implementation of measures for the prevention and spill of dangerous goods is an important aspect of sustainable development of railway transport. oil spills accident are the most dangerous. They are accompanied by significant pollution of all environmental objects. Studying and development of oil localization and clean-up technologies of such accidents is an important problem of environmental protection to modern conditions of railway transport development. The purpose: to improve the effectiveness of traditional methods of oil spill elimination and the development of new clean-up technologies adapted to the real conditions of the railway transport of Ukraine. Methods: To achieve the research purposes was used analysis of material flows, typical for places emergence and localization of the oil spill on the railways. Results: Analysis of standard technological scheme for the oil spills eliminations has shown that the most difficult task of effective clean-up surfaces is the timely delivery of oil sorbents and special equipment to the area spill containment. The general effectiveness of the elimination activities specifies the time from the beginning contact of dangerous goods with environmental objects to the absorption it into the structure of sorbent . Us was developed the technological scheme of oil spill elimination. This scheme provide a permanent and fast access to the sorbents into the oil spill localization area. It was proposed to device that allows you to transport the sorbent into sorption booms directly on the tank for transportation of petroleum products. Conclusions: Preventative accumulation of sorbents to the oil spill elimination into the localization area provides the organizational and operational simplicity of all stages of clean-up technology. Technical and economic assessment shows that the proposed technology is effective, technologically feasible and economically competitive.